2022
DOI: 10.3389/fcell.2022.874846
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Soluble Transferrin Receptor Levels Were Associated With High Prevalence of Cardiovascular Diseases: Insights From the National Health and Nutrition Examination Survey 2017–2018

Abstract: Background: Iron deficiency is common in cardiovascular diseases (CVD), e.g., heart failure and coronary heart disease. Soluble transferrin receptor (sTfR) is a promising marker representing unmet cellular iron demands. However, whether higher serum sTfR is associated with increased risk of CVDs needs further investigation.Methods: In the present cross-sectional study, we analyzed data of 4,867 adult participants of the National Health and Nutrition Examination Survey (NHANES) 2017–2018. Linear regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Nevertheless, the incidence of hereditary methylmalonic acidemia was very low in the general population, therefore it is unlikely to alter the result. Third, same to the previous studies ( 42 , 43 ), CVDs were identified by self-reporting, which may elicit recall and interviewer bias. But the diagnosis of CVDs was consistent throughout the study.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, the incidence of hereditary methylmalonic acidemia was very low in the general population, therefore it is unlikely to alter the result. Third, same to the previous studies ( 42 , 43 ), CVDs were identified by self-reporting, which may elicit recall and interviewer bias. But the diagnosis of CVDs was consistent throughout the study.…”
Section: Discussionmentioning
confidence: 96%
“…19 Elevated sTfR levels are associated with a higher prevalence of cardiovascular disease. 20 In the Chinese Health and Nutrition Examination Survey study, sTfR levels were shown to be positively correlated with systolic and diastolic blood pressure at baseline, and high sTfR levels independently predicted hypertension onset. 21 Therefore, elevated sTfR in GDM+PE patients shares a common pathway with cardiovascular diseases in elderly individuals, as pregnancy might predispose women to a high risk of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 98%
“…The concentration of sTFR can re ect the demand of cells for iron and is a good indicator of functional iron de ciency [31,32]. In recent years, many studies have shown that elevated sTFR levels were associated with the high prevalence of cardiovascular diseases [33,34]. In the 24th week, although the proportion of patients with absolute iron de ciency did not increase signi cantly, the sTFR level increased signi cantly, suggesting that iron de ciency occurred in PD patients with the increase in iron utilization, and appropriate iron supplementation may be necessary.…”
Section: Discussionmentioning
confidence: 99%